SUPPLEMENTATION OF MULBERRY LEAVES WITH PROBIOTIC BIFILAC ON ECONOMIC TRAITS OF SILKWORM (BOMBYX MORI L.) (International Journal of Food and Nutritional Sciences, 2022)
Silkworm b.mori. is one of the most important beneficial insects. One of the most important characteristics of the silkworm B. mori L. is its ability to switch plant proteins from feeding material to silk proteins. Silkworm is a typical monophagous insect and mulberry (Morus spp.) leaf is its sole food. Probiotic are viable, nonpathogenic microorganisms which when supplementation in adequate amounts, confer a health benefit on the host. In the present study aimed toinvestigating the rearing performance and economic parameters of the silkworm when the larvae supplemented with probiotic bifilacatthree (1%, 2% and 3%) different concentration. Among the treatments,2% recorded maximum larval weight (5.39 g), effective rate rearing (96.85 %), cocoon weight (1.81 g), shellweight (0.408 g), silk length (876.43 m), silk weight(0.378 g) and finer denier (3.88) besides reduced larval mortality (3.64 %) due to disease incidence compared to control. The outcome of the study indicated that, there is profound increase due to probiotictreatment in larval growth and cocoon characters than the control with enhanced and quality silk production.